2022
DOI: 10.3389/fimmu.2022.818630
|View full text |Cite
|
Sign up to set email alerts
|

Pro Nerve Growth Factor and Its Receptor p75NTR Activate Inflammatory Responses in Synovial Fibroblasts: A Novel Targetable Mechanism in Arthritis

Abstract: We have recently provided new evidence for a role of p75NTR receptor and its preferential ligand proNGF in amplifying inflammatory responses in synovial mononuclear cells of chronic arthritis patients. In the present study, to better investigate how activation of the p75NTR/proNGF axis impacts synovial inflammation, we have studied the effects of proNGF on fibroblast-like synoviocytes (FLS), which play a central role in modulating local immune responses and in activating pro-inflammatory pathways. Using single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…These results correlate with the evidence that intranasal NGF delivered in adult rats after TBI, promoted an anti‐inflammatory response, decreasing brain IL‐1β and TNF‐α, and limiting the activation of NF‐κB (Lv et al, 2013). Our recent work on the link between the endogenous NGF system and the development of chronic peripheral inflammation (Farina et al, 2022), suggests that interfering with the balance between different forms of NGF (mature, as distinct from precursor) may indeed affect the development of inflammatory processes. An in‐depth analysis of endogenous NGF/proNGF activity and regulation after TBI is therefore warranted, because our therapeutic intervention may shift the balance of different forms of NGF toward the mature moiety, positively affecting both neuroinflammation and glial phenotype (Barcelona et al, 2016; Cheng et al, 2020; Rizzi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These results correlate with the evidence that intranasal NGF delivered in adult rats after TBI, promoted an anti‐inflammatory response, decreasing brain IL‐1β and TNF‐α, and limiting the activation of NF‐κB (Lv et al, 2013). Our recent work on the link between the endogenous NGF system and the development of chronic peripheral inflammation (Farina et al, 2022), suggests that interfering with the balance between different forms of NGF (mature, as distinct from precursor) may indeed affect the development of inflammatory processes. An in‐depth analysis of endogenous NGF/proNGF activity and regulation after TBI is therefore warranted, because our therapeutic intervention may shift the balance of different forms of NGF toward the mature moiety, positively affecting both neuroinflammation and glial phenotype (Barcelona et al, 2016; Cheng et al, 2020; Rizzi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using single-cell RNA sequencing has found that fibroblast-like synoviocyte (FLS) from active patients with RA overexpressed p75 NTR and sortilin compared with patients with RA in the remission stage ( 95 ). P75 NTR was significantly enriched in PRG4 pos lining FLS and THY1 pos COL1A1 pos sublining FLS, as well as remarkably expressed in FLS ( 95 ). After IL-1β stimulation in vitro , the expression level of p75 NTR on FLS of patients with RA was significantly upregulated.…”
Section: Probdnf and Its Receptors In Ramentioning
confidence: 99%
“…After IL-1β stimulation in vitro , the expression level of p75 NTR on FLS of patients with RA was significantly upregulated. Consequently, p75 NTR signaling activated the inflammatory response in FLS, and neutralizing, or inhibiting p75 NTR could reduce the inflammatory factors IL-6, IL-8, and MCP1 in FLS, which was related to the activation of downstream JNK/p38 MAPK signaling ( 95 ). Chronic glucose metabolic changes induced by hypoxia and inflammatory mediators in FLS and synovial T cells will activate many signaling pathways, including MAPK, NF-κB, and PI3K/Akt pathways ( 96 ), which are crucial for the expression of adhesion molecules, secretion of cytokines, and inhibition of apoptosis, as well as for migration and invasion ( 96 ) ( Figure 4 ).…”
Section: Probdnf and Its Receptors In Ramentioning
confidence: 99%
“…Dysmetabolism, stress, and inflammation have showed to alter the NGF expression [ 29 ] and, like in brain and retina [ 30 , 31 , 32 ], an unbalance of NGF and proNGF expression has been recently proposed as a risk factor for peripheral diseases, also associated with inflammation [ 33 , 34 ]. There is currently no data on proNGF processing including the pdNGFpeps, in the central nervous system or peripheral tissues, and neither it is known whether inflammatory conditions might affect the relative expression of the pdNGFpeps.…”
mentioning
confidence: 99%